Log P Determines Licorice Flavonoids Release Behaviors and Classification from CARBOMER Cross-Linked Hydrogel - Zhuxian Wang; Yi Hu; Yaqi Xue; Zhaoming Zhu; Yufan Wu; Quanfu Zeng; Yuan Wang; Chunyan Shen; Qun Shen; Cuiping Jiang; Li Liu; Hongxia Zhu; et al. (MDPI AG, 2022)
The dynamic drug release mechanisms from Carbomer 940 (CP) hydrogels have not been systematically explored elsewhere. This study aimed to investigate the quantitative structure−activity relationship of licorice flavonoids (LFs) compounds on their drug release from CP hydrogels based on LFs-CP interactions and drug solubility in the release medium. Ten LFs-CP hydrogels were formulated, and their in vitro release study was conducted. The intermolecular forces of LFs-CP systems were characterized by FTIR, molecular docking and molecular dynamic simulation. Ten LFs compounds were classified into I (high-release capability) LFs and II (low-release capability) LFs according to the different negative correlations between drug release percent at 48 h and intermolecular forces of drugs-CP, respectively. Moreover, high-release LFs possessed significantly lower log P and higher drug solubility in the release medium than low-release LFs. All I LFs release behaviors best followed the first-order equation, while II LFs release characteristics best fitted the zero-order equation except for isoliquiritigenin. Log P mainly affect the hydrogel relaxation process for I drugs release and the drug diffusion process for II drugs release. Higher log P values for LFs resulted in higher intermolecular strength for I drugs-CP systems and lower drug solubility in the release medium for II drugs, which hindered drug release. Hydrophobic association forces in drug-CP hydrogel played a more and more dominant role in hindering I LFs release with increasing release time. On the other hand, lower drug solubility in the release medium restricted II LFs release, and the dominant role of drug solubility in the release medium increased in 24 h followed by a significant decline after 36 h. Collectively, log P of LFs served as a bridge to determine LFs compound release behaviors and classification from CP hydrogels, which provided guidelines for reasonable design of LFs hydrogels in pharmaceutical topical formulations.